The Concept of Law in Abrahamic Religions - Mursalova, Aliya (Scholarya Demo Journal of Ruby, 2018)
In order to accept the world as it is, we need religious literacy. We should have an idea of the basic beliefs and practices of world religions. This article is an attempt to offer a religious educational program. It presents the study of the legal system of these religions, their sources, solutions and methods. There are many examples showing both the differences and similarities between them. Moreover, it describes the reflection of various aspects of human life in the Abrahamic religions. The solution of legal problems of a person in different religions is studied in the paper. This is a competent presentation of the basic legal ideas, practices and values of the three religions. The article discusses various concepts in the rights of the main three religions of the world in an accessible and logically aligned form. The structure of the article, modem sources, nature and sequence of presentation are intended to contribute to the most adequate development of the religions’ foundations, however, a special place was given to the consideration of the legal foundations of the Abrahamic religions. In addition, it describes the appearance of the religions chronologically, starting from Judaism, Christianity to Islam. This greatly facilitates an ability to trace the chronological path and evolution of religious legislation.